Strategi Manajemen Pemasaran Pendidikan di SMA N 1 Cepogo - Maya Sofia Fatima Azzahra; Muhammad Nur Cahyono (Journal of Islamic Education Leadership, 2023)
Education Marketing Management Strategy at SMAN 1 Cepogo. Along with the development of today's increasingly modern era, especially for educational institutions at SMA Negeri 1 Cepogo are required to be able to compete in meeting the needs of the community. Educational institutions at SMA Negeri 1 Cepogo must be able to improve continuously in the aspect of education to improve the quality of education even better. Therefore, marketing management must be managed optimally to be able to compete with other educational institutions. The purpose of this study is to find out how the marketing strategy is appropriate, the implementation of the marketing strategy and the supporting and inhibiting factors of marketing management in SMA Negeri 1 Cepogo. The research method used here refers to a descriptive qualitative method by making direct observations at SMA Negeri 1 Cepogo which is then followed up by conducting interviews with a group of people and one of the admin staff who deals with marketing management, interviews here by taking and collecting data obtained in a short period of time simultaneously. The results of this study are that the marketing strategy carried out by SMA Negeri 1 Cepogo is carried out using social media and direct outreach. Apart from that, marketing strategy implementation is carried out by making brochures and direct outreach to the public. The supporting factors are the support and fulfillment of facilities from the school, while the inhibiting factors in submitting purchases of goods are very difficult due to the fact that they have to make the details requested from the treasurer